Assessing the dimensionality of student school engagement survey : support for a multidimensional bifactor model - Inman, Richard A. (2020)
This document is the authors’ version of the final accepted manuscript, published online in 27.4.2020 by Revista de Psicodidáctica (English ed.). doi: 10.1016/j.psicoe.2020.03.001 https://www.sciencedirect.com/science/article/pii/S253038052030006X